Set up errors in Brain tumours – A retrospective study to review the current practice of PTV margins in the institution - Diksha Chaturvedi; Ankita Mehta; Piyush Kumar (International Journal of Medical Research and Review, 2022)
Set up errors in Brain tumours – A retrospective study to review the current practice of PTV margins in the institution Chaturvedi D.1 , Mehta A.2 , Kumar P.3* 1 Diksha Chaturvedi, Junior Resident, Department of Radiation Oncology, Shri Ram Murti Institute of Medical Sciences, Bareilly, Uttar Pradesh, India. 2 Ankita Mehta, Senior Resident, Department of Radiation Oncology, Shri Ram Murti Institute of Medical Sciences, Bareilly, Uttar Pradesh, India. 3* Piyush Kumar, Professor and Head, Department of Radiation Oncology, Shri Ram Murti Institute of Medical Sciences, Bareilly, Uttar Pradesh, India. Corresponding Author: Dr. Piyush Kumar, Professor and Head, Department of Radiation Oncology, all authors are affiliated to Shri Ram Murti Institute of Medical Sciences, Bareilly, Uttar Pradesh, India, E-mail: piykumagr@gmail.com Abstract Background Radiotherapy in brain tumors needs accuracy and reproducibility of the patient’s position. There may be set up errors which are taken care by adding planning target volume (PTV) margin. Lesser PTV margins may lead to tumor miss or greater margins may lead to unnecessary radiation of normal brain tissue. The present study is done to evaluate whether the current practice of PTV margins in our institute is optimum or not. Materials and methods Eleven patients of brain tumours who received adjuvant radiotherapy were retrospectively selected for determining the setup errors. These patients were immobilised in supine position and contrast enhanced CT of head was taken for radiotherapy planning. Delineation of gross tumor volume and clinical target volume was done with 5 mm PTV margin. The treatment was delivered by 3-Dimensional Conformal Radiotherapy or Intensity Modulated Radiotherapy Technique. The set up errors in three dimensions were determined retrospectively for all images. PTV margins were calculated using International Commission on Radiation Units And Measurements Report 62, Stroom’s and Van Herk formulae. Results The overall population set up error was 0.034,-0.048, 0.028 in X, Y, Z directions respectively. The population systematic error was calculated to be 0.107, 0.069, 0.092 and population random error was 0.221, 0.202, 0.217 in X, Y, Z directions respectively. The calculated setup margin as per the three formulas was less than 5 mm in all directions. Conclusion The present study showed that the institutional protocol of 5 mm is optimum to counter the setup errors.